Польсько-українські міждержавні взаємини у світлі новітніх викликів та ризиків (2015-2017 рр.) - Чорна, Н. (Міжнародні зв’язки України: наукові пошуки і знахідки, 2017)
Проаналізовано польсько-українські міждержавні відносини в період,
що розпочався з приходом до влади в Республіці Польща президента
А. Дуди, а пізніше — перемогою на парламентських виборах праворадикальної політичної партії «Право і справедливість». Увагу зосереджено на ключових тенденціях їхнього розвитку та чинниках, що на них
впливають. З’ясовано наслідки, що їх для взаємин між двома державами
має акцентування офіційної Варшави на проблемах спільної минувшини,
головним чином Волинської трагедії, трактування якої українською та
польською сторонами є далеко не тотожним. Доведено, що попри напруження, спричинене часто резонансними кроками польської та української влади, стратегічне партнерство між нашими двома державами
продовжує зберігати свою актуальність. Polish-Ukrainian interstate relations covering the period beginning with
the presidency of A. Duda and followed by the victory of the radical-right
political party «Law and Justice» in the parliamentary elections have been
analyzed. The main attention is focused on the key trends of their development
and the factors affecting them. The consequences to the relations between the
two countries of the emphasis that official Warsaw makes on issues of the
common past, mainly Volyn tragedy, the interpretation of which on Ukrainian
and Polish sides are far from identical, have been found out. The attention is
drawn to the adoption of the law «On the legal status and honoring the
memory of the fighters for Ukraine’s independence in the twentieth century» by
the Verkhovna Rada of Ukraine (April 9, 2015), wich caused an active
discussion on the part of the official Warsaw, as well as to the similarly met in
Ukraine resolution of the Sejm «On establishing the 11 of July the Memorial
Day of Poles, the victims of genocide committed by the UPA» (22 July 2016).
The provocations on both sides of the border organized by the interested in
worsening of the relations between Warsaw and Kyiv have been highlighted.
However, іt has been proven that despite the tensions caused by the often highprofile
steps of the Polish and Ukrainian authorities, the strategic partnership
between the two countries remains relevant. And while the first official visit of
President A. Duda t to Ukraine took place only in December of 2015, the fact
is, that the presence of the Polish head of state at the ceremony in Kyiv on the
occasion of the 25th anniversary of Ukraine’s independence on August the
24th of 2016 only six months after the election is an eloquent testimony of the
importance of cooperation with Ukraine for the official Warsaw. Precisely then
the presidents of the neighboring states signed a Joint Declaration on Strategic
Partnership.